Oral health knowledge, attitudes, and practices of paediatric nurses caring for hospitalized children - Ashley Fletcher; Shauna Hachey; Shauna Hachey; Tracy Doyle; Tracy Doyle (Frontiers Media S.A., 2024)
ObjectivesNurses are well positioned to provide oral care to hospitalized children. This study explores pediatric hospital nurses' knowledge, attitudes, practices and perceived barriers to providing oral care.MethodsUsing a descriptive cross-sectional design, previously validated surveys were adapted based on input from key stakeholders and administered to all nurses and staff providing patient care on inpatient units (N = 239) of a pediatric hospital.ResultsThe survey response rate was 40% (N = 96), providing a margin of error of 7.59% (95% C.I.). Most participants were unaware that caries is infectious (51%, n = 49) and caries-producing bacteria is transmissible (35%, n = 34). The majority (57%, n = 52) of participants did not recall oral care content within their formal education or oral care continuing education (88%, n = 81), despite high interest (87%, n = 80). Oral care was rated by most as a priority (85%, n = 81), yet the majority (74%, n = 69) believed it is under performed. More nurses with 6 or more years of experience placed a high or very high value on prioritizing oral health (p = 0.005). Furthermore, most nurses do not assess oral health on admission (63%, n = 60), routinely incorporate oral health into the care plan (45%, n = 43), or document oral care (60%, n = 56). Commonly reported barriers include lack of patient cooperation, medical status, and competing needs.Conclusions and outcomeDespite nurses valuing the importance of oral care and their willingness to learn, oral care practices are lacking, and barriers exist. Future investigation is required to further explore the findings related to barriers to care and lack of practice. These results and future findings will be used to guide institutional oral care policy and education.